Evaluation The Kidney Failure Test in SLE Patients by Using SLEDAI and Cys.C Index - Al-Masudi, Hadi R. Hasan; Al-Hashimy, Noor H.; Mahdi, Mohammad S. (Scientific Journal of Medical Research, 2019)
Objectives: This study aims to explore the association of serum urea, creatinine and uric acid with clinical and laboratory characteristics in SLE patients, independent of lupus renal involvement. Methods: Sixty of systemic lupus erythematosus patients that diagnosed by clinic specialists by using (SLEDAI) taken from (Al-Hussein Medical City/Kerbala / IRAQ). During the period from January 2015 to December 2016. thirty healthy persons who matched of gender and age with patients as a control group, and haven’t history for this disease. Results: The result shows that the biochemical test depend on Cys.C index significant increase in progressive SLE patient especial in lupus nephritis in the Cys. C test than SLEDAI and this increasing related with creatinine. The mean of Cys.C test in progressive and lupus nephritis (2.11 ±0.17 ; 3.72 ±0.72) compared with SLEDAI (2.17 ±0.70 ; 2.83 ±1.19). The mean of creatinine in progressive and lupus nephritis (0.78 ±0.22 ; 1.55 ±0.86) compared with SLEDAI (0.85 ±0.25; 1.35 ±0.65) respectively. Conclusion: Cystatin C is a good marker for pre-diagnosis test of kidney failure to detection lupus nephritis and related with creatinine in SLE patients.